Microbial fuel cells - Ganesh Nithyaseelan (2011)
Microbial fuel cells (MFC) are very promising for bioelectricity generation and bioremediation, which can efficiently convert organic wastes into electricity (wastes to energy). Biofilm formation on the anode of MFC is essential for the transfer of electron from bacteria to the anode, thereby power generation. We are interested in experimentally growing anodic biofilm of different bacterial strains, e.g, Escherichia coli, Pseudomonas aeruginosa, and Geobacter, and testing their electrical conductivity. We aim to engineer these biofilms for the optimization of power output of MFC.